From Control to Social Reform: The Latin-American Social Question in the Latin-American Scientific Congresses (1898-1908) [Do Controle À Reforma Social: A Questão Social Nos Congressos Científicos Na América Latina (1898-1908)] [del Control a la Reforma Social: La Cuestión Social en Los Congresos Científicos Latinoamericanos (1898-1908)] - Castillo-Armijo, P (Editora da P U C R S, 2016)
This article focuses on the circulation of ideas on social policies in Latin America through the discussions in the Latin-American scientific congresses. The main argument is that, although Latin-American scholars relied on European narratives to frame the social problems that affected the region, the policy solutions they found were not based on the direct importation of foreign models. Either by emphasising criminality or the need for social reform, scholars sought to address the social question through regional mechanisms which were the outgrowth of regional processes of knowledge transfer. © 2016, Editora da P U C R S. All rights reserved.